Iowa Birdline Update, January 1, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Notes for the Iowa Birdline update for January 1, 1990. Highlights of the update include a new sighting of a Bohemian Waxwing and the continued presence of Eurasian Tree Sparrows, Townsend's Solitaires, and a Long-tailed Duck. Also of note were observations of several species of Owls, including Long-eared Owls, Short-eared Owls, and Saw-whet Owls. In addition, a report from the Keokuk Christmas bird count of 267 Bald Eagles. Epson - sheet feed/flatbed